2011
DOI: 10.1007/s00595-010-4279-z
|View full text |Cite
|
Sign up to set email alerts
|

Primary infected abdominal aortic aneurysm: Surgical procedures, early mortality rates, and a survey of the prevalence of infectious organisms over a 30-year period

Abstract: In situ replacement with excision of infected tissue, lavage using 10 l saline solution, and omentum plasty for PIAAA successfully resolved the condition. High local concentrations of rifampin-soaked grafts or superficial femoral vein may also be an alternative for an in situ replacement conduit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(52 citation statements)
references
References 33 publications
0
48
0
4
Order By: Relevance
“…Prevalence and etiology Mycotic aneurysms reflect fewer than 1% of aortic aneurysms that are surgically repaired, are more common in men, and are more likely to rupture than non-infected aneurysms (2)(3)(4)(5). Mycotic aneurysms are more likely to occur in the aorta than other arteries (6)(7)(8).…”
Section: Mycotic Aneurysmsmentioning
confidence: 99%
“…Prevalence and etiology Mycotic aneurysms reflect fewer than 1% of aortic aneurysms that are surgically repaired, are more common in men, and are more likely to rupture than non-infected aneurysms (2)(3)(4)(5). Mycotic aneurysms are more likely to occur in the aorta than other arteries (6)(7)(8).…”
Section: Mycotic Aneurysmsmentioning
confidence: 99%
“…In addition, we used the rifampicinsoaked gelatin-sealed Dacron graft for axillo-bifemoral bypass. Recent studies show the satisfactory outcomes of in-situ reconstruction, [5][6][7][8] and this procedure also can be an effective surgical alternative for the treatment of primary infected abdominal aortic aneurysm. Rifampicinsoaked graft 5,6) or polytetrafluoroethylene graft 7) is an available conduit for the prevention of postoperative graft infection.…”
Section: Discussionmentioning
confidence: 98%
“…Some authorities recommend extending the incubation of blood cultures for up to 2 weeks to enable detection of slowly growing organisms (Francioli et al, 1985). Published studies show that when biopsy cultures from the aneurysm wall and blood cultures are done, at least one is positive in 66-100% of patients (Maeda et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Brossier et al (2012) described five cases in which they used IV antibiotics for 30 days followed by oral antibiotics for 52 weeks but did not mention the antibiotics used. Maeda et al (2011) reported three cases and used IV antibiotics for only 2-4 weeks until the WBC count and CRP were normal; all patients were alive at 1 year. Hagiya et al (2014) used IV ceftriaxone 2 gram daily and ciprofloxacin 300 mg Q12h for 36 days followed by long term oral ciprofloxacin but did not describe the dose and duration of ciprofloxacin in their patient.…”
Section: Discussionmentioning
confidence: 99%